Synergetic enhancement of selectivity for electroreduction of CO2 to C2H4 by crystal facet engineering and tandem catalysis over silver-incorporated-cuprous oxides - Gang Dong; Chuang Xue; Meng Li; Tiantian Zhang; Dongsheng Geng; Li-Min Liu (Materials Reports: Energy, 2023)
Electrochemical CO2 reduction to C2H4 can provide a sustainable route to reduce globally accelerating CO2 emissions and produce energy-rich chemical feedstocks. However, the poor selectivity in C2H4 electrosynthesis limits its implementation in industrially interesting processes. Herein, we report a composite structured catalyst composed of Ag and Cu2O with different crystal faces to achieve highly efficient reduction of CO2 to C2H4. The catalyst composed of Ag and octahedral Cu2O enclosed with (111) facet exhibits the best CO2 electroreduction performance, with the Faradaic efficiency (FE) and partial current density reaching 66.8% and 17.8 mA cm−2 for C2H4 product at −1.2 VRHE in 0.5 M KHCO3, respectively. Physical characterization and electrochemical test analysis indicate that the high selectivity for C2H4 product stems from the synergistic effect of crystal faces control engineering and tandem catalysis. Specifically, Ag can provide optimal availability of CO intermediate by suppressing hydrogen evolution; subsequently, C–C coupling is promoted on the intimate surface of Cu2O with facet-dependent selectivity. The insights gained from this work may be beneficial for designing efficient multicomponent catalysts for improving the selectivity of electrochemical CO2 reduction reaction to generate C2+ products.